The Synergistic Effects of Sulfated Lactosyl Archaeol Archaeosomes When Combined with Different Adjuvants in a Murine Model - Yimei Jia (Pharmaceutics, 2021)
Archaeosomes, composed of sulfated lactosyl archaeol (SLA) glycolipids, have been proven to be an effective vaccine adjuvant in multiple preclinical models of infectious disease or cancer. SLA archaeosomes are a promising adjuvant candidate due to their ability to strongly stimulate both humoral and cytotoxic immune responses when simply admixed with an antigen. In the present study, we evaluated whether the adjuvant effects of SLA archaeosomes could be further enhanced when combined with other adjuvants. SLA archaeosomes were co-administered with five different Toll-like Receptor (TLR) agonists or the saponin QS-21 using ovalbumin as a model antigen in mice. Both humoral and cellular immune responses were greatly enhanced compared to either adjuvant alone when SLA archaeosomes were combined with either the TLR3 agonist poly(I:C) or the TLR9 agonist CpG. These results were also confirmed in a separate study using Hepatitis B surface antigen (HBsAg) and support the further evaluation of these adjuvant combinations.